Advertisement Remove all ads

(1 + X) Y Dx + (1 + Y) X Dy = 0 - Mathematics

Sum

(1 + xy dx + (1 + yx dy = 0

Advertisement Remove all ads

Solution

We have,

(1 + xy dx + (1 + yx dy = 0

\[\frac{dy}{dx} = - \frac{y\left( 1 + x \right)}{x\left( 1 + y \right)}\]

\[ \Rightarrow \left( \frac{1 + y}{y} \right)dy = - \left( \frac{1 + x}{x} \right)dx\]

\[ \Rightarrow \left( \frac{1}{y} + y \right)dy = - \left( \frac{1}{x} + 1 \right)dx\]

Integrating both sides, we get

\[\int\left( \frac{1}{y} + 1 \right)dy = - \int\left( \frac{1}{x} + 1 \right)dx\]

\[ \Rightarrow \int\frac{1}{y}dy + \int dy = - \int\frac{1}{x}dx - \int dx\]

\[ \Rightarrow \log\left| y \right| + y = - \log\left| x \right| - x + C\]

\[ \Rightarrow \log\left| xy \right| + y + x = C\]

\[ \Rightarrow x + y + \log\left| xy \right| = C\]

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 12 Maths
Chapter 22 Differential Equations
Revision Exercise | Q 27 | Page 145
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×